2018
DOI: 10.1038/s41598-018-29373-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally induced metamorphosis in highly regenerative axolotl (ambystoma mexicanum) under constant diet restructures microbiota

Abstract: Axolotl (Ambystoma mexicanum) is a critically endangered salamander species and a model organism for regenerative and developmental biology. Despite life-long neoteny in nature and in captive-bred colonies, metamorphosis of these animals can be experimentally induced by administering Thyroid hormones (THs). However, microbiological consequences of this experimental procedure, such as host microbiota response, remain largely unknown. Here, we systematically compared host bacterial microbiota associated with ski… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 71 publications
2
32
0
Order By: Relevance
“…For a better understanding of such morphological changes in axolotl, a comprehensive histological atlas of the morphological alterations taking place within tissues and organs throughout metamorphosis has been described (Demircan et al 2016) . In addition to morphological and histological changes, metamorphosis of axolotl brings about a sharp reduction in regeneration rate, and leads to carpal and digit malformations (Monaghan et al 2014;Demircan et al 2018). Obtained results from axolotl are well aligned with the previous studies on Xenopus laevis which demonstrate dramatic restriction in regenerative capacity with metamorphosis (Mescher and Neff 2006;Godwin and Rosenthal 2014) .Furthermore, studies on regenerationdeficient animal models suggest that there is a correlation between cellular changes during ontogenic development and progressive loss of regenerative ability (Seifert et al 2012;Lee-Liu et al 2018) .…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…For a better understanding of such morphological changes in axolotl, a comprehensive histological atlas of the morphological alterations taking place within tissues and organs throughout metamorphosis has been described (Demircan et al 2016) . In addition to morphological and histological changes, metamorphosis of axolotl brings about a sharp reduction in regeneration rate, and leads to carpal and digit malformations (Monaghan et al 2014;Demircan et al 2018). Obtained results from axolotl are well aligned with the previous studies on Xenopus laevis which demonstrate dramatic restriction in regenerative capacity with metamorphosis (Mescher and Neff 2006;Godwin and Rosenthal 2014) .Furthermore, studies on regenerationdeficient animal models suggest that there is a correlation between cellular changes during ontogenic development and progressive loss of regenerative ability (Seifert et al 2012;Lee-Liu et al 2018) .…”
Section: Introductionsupporting
confidence: 81%
“…While animals such as zebrafish, lizards, and urodeles are able to regenerate some of their extremities even after reaching adulthood, frogs and mammals lose this ability prior to metamorphosis (Seifert et al 2012) or during post embryonic development. Although neotenic axolotls have an exceptional regenerative capacity, previous studies (Demircan et al 2018(Demircan et al , 2019 have shown defective and infidel limb regeneration of axolotl after metamorphosis. Since findings of published studies underlined an apparent delay in phases of regeneration for metamorphic animals, in this study we aimed to reveal the gene expression pattern at early phases of regeneration (day0,1,4 and 7) for both neotenic and metamorphic axolotls at the protein level.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It's been suggested that, unlike the amniote vertebrate, the successive regenerative capacity of axolotls may be driven by a weak inflammatory response due to their simpler adaptive immune system [1,10]. In response to experimental induction of metamorphosis via thyroid hormone administration, diminished regenerative power of axolotls is observed for some body parts such as appendages [11,12], while such regenerative potential seems to be unobstructed for other parts of the body [1,13].…”
Section: Introductionmentioning
confidence: 99%